2003
DOI: 10.1200/jco.2003.05.062
|View full text |Cite
|
Sign up to set email alerts
|

Colon Cancer Survival Is Associated With Increasing Number of Lymph Nodes Analyzed: A Secondary Survey of Intergroup Trial INT-0089

Abstract: The number of lymph nodes analyzed for staging colon cancers is, itself, a prognostic variable on outcome. The impact of this variable is such that it may be an important variable to include in evaluating future trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
663
10
60

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,028 publications
(759 citation statements)
references
References 16 publications
26
663
10
60
Order By: Relevance
“…This, along with the associated greater lymph node yield, may partially explain the high 5-year survival rates reported in Erlangen [13]. There was an increase in the number of negative lymph nodes with CME and CVL which has been linked to improved survival in both lymph node negative cases [14,15] and stage III disease [16]. West et al reported a greater lymph node yield (median, 30 vs. 18; p<0.0001) in high versus low ligation [13] In our study, the corresponding values are 33 and 25 (p= 0.048), thus establishing that high ligation produces oncologically superior specimen compared with standard low ligation surgery for carcinoma of the left colon and rectum.…”
Section: Discussionmentioning
confidence: 96%
“…This, along with the associated greater lymph node yield, may partially explain the high 5-year survival rates reported in Erlangen [13]. There was an increase in the number of negative lymph nodes with CME and CVL which has been linked to improved survival in both lymph node negative cases [14,15] and stage III disease [16]. West et al reported a greater lymph node yield (median, 30 vs. 18; p<0.0001) in high versus low ligation [13] In our study, the corresponding values are 33 and 25 (p= 0.048), thus establishing that high ligation produces oncologically superior specimen compared with standard low ligation surgery for carcinoma of the left colon and rectum.…”
Section: Discussionmentioning
confidence: 96%
“…There is a controversy, however, in the literature about whether the number of lymph nodes resected and evaluated impacts patient outcomes [29,30]. Further ambiguity exists even among the proponents of this quality metric regarding the exact number of lymph nodes needed to accurately stage a patient with colon cancer [5,[7][8][9][10][11][12][13][14][15][16][17][18]. Still, in the absence of a unique molecular signature of a colon tumor that dictates therapies and predicts a patient's course, the American College of Surgeons, ASCO, NCCN and others have adopted this as an indicator for quality assessment [24,26].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
“…There has been great discussion and variability in the literature about the number of nodes that need to be examined to stage patients with accuracy [5,[7][8][9][10][11][12][13]. In addition, a substantial body of literature suggests that the absolute number of lymph nodes removed, whether positive or negative, is independently correlated with survival [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…3 Furthermore, a large prospective trial and several population-based studies reported that an increase in the number of lymph nodes sampled could improve survival through accurate staging and consequently tailored treatments. [4][5][6] A large body of research has documented that shortterm surgical complications and long-term survival are correlated with hospital volume. [7][8][9] Surgery-related mortality can be avoided if cancer surgeries are performed by high-volume hospitals.…”
Section: Introductionmentioning
confidence: 99%